2017
DOI: 10.1186/s12891-017-1542-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of manual handling operations at work with the key indicator method (KIM-MHO) — determination of criterion validity regarding the prevalence of musculoskeletal symptoms and clinical conditions within a cross-sectional study

Abstract: BackgroundManual handling operations (MHO) are known to be risk factors for work-related upper limb disorders (WRULDs), e.g. symptoms and conditions such as carpal tunnel syndrome. To estimate the risk of WRULDs, a Key Indicator Method (KIM) for the risk assessment of MHO was developed. The method was validated in regard to different criteria, including face validity, criterion validity, reliability and further aspects concerning utility. This paper describes the KIM-MHO and criterion validity of this method w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 36 publications
0
12
0
3
Order By: Relevance
“…This approach allows a more comprehensive task assessment, integrating a wide range of musculoskeletal risk factors. Considering four preassembly workers and the observation of several work cycles, a total of 40 postures were assessed by the following methods: [32]; (ii) Revised Strain Index (RSI) [33]; (iii) Key Indicator Method for assessing physical workload during Manual Handling Operations (KIM-MHO) [34].…”
Section: Assessment Of Physical Ergonomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach allows a more comprehensive task assessment, integrating a wide range of musculoskeletal risk factors. Considering four preassembly workers and the observation of several work cycles, a total of 40 postures were assessed by the following methods: [32]; (ii) Revised Strain Index (RSI) [33]; (iii) Key Indicator Method for assessing physical workload during Manual Handling Operations (KIM-MHO) [34].…”
Section: Assessment Of Physical Ergonomicsmentioning
confidence: 99%
“…We also applied the KIM-MHO method because the preassembly tasks are frequently associated with Work-related Upper-Limb Disorders (WULD), such as carpal tunnel syndrome. Klussmann et al [34] demonstrated that KIM-MHO risk scores have a statistically significant correlation to the prevalence of musculoskeletal symptoms (assessed by Nordic questionnaire) and clinical conditions in the shoulder, elbow and hand-wrist body regions between more than 600 employees exposed to MHO. Its application is, therefore, deemed relevant to this study due to the type of selected tasks and the clinical background of musculoskeletal problems in upper limbs among the selected workers.…”
Section: Assessment Of Physical Ergonomicsmentioning
confidence: 99%
“…In Deutschland wurde der NMQ von Caffier et al [16] in einer deutschen, aber nicht validier-ten, Version vorgestellt. Der NMQ wurde in Deutschland in verschiedensten Studien in modifizierten Versionen eingesetzt [17][18][19][20][21][23][24][25] und für die betriebliche Praxis empfohlen [26]. Für Deutschland existiert derzeit keine standardisierte Übersetzung oder validierte Version des NMQ.…”
Section: Hintergrund Und Fragestellungunclassified
“…However, this method allows a global postural assessment for each task, considering the most frequent postures (so the final result is not calculated as a mean value as done for RULA assessment). Klussmann et al [33] demonstrated that KIM-MHO risk scores are significantly related to the prevalence of musculoskeletal symptoms (assessed by Nordic questionnaire) and clinical conditions especially in the shoulder, elbow and hand/wrist body regions among more than 600 employees exposed to MHO. Therefore, its application is relevant at the current study, since the tasks assessed are MHO and the selected workers have musculoskeletal problems at hand/wrist.…”
Section: Preassembly Workers and Worktationmentioning
confidence: 99%